2012
DOI: 10.1111/bjh.12005
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of arterial thromboembolism after a prior episode of venous thromboembolism: results from the Prevention of REnal and Vascular ENd stage Disease (PREVEND) Study

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. SummaryLarge population-based studies are needed to establish the magnitude and duration of the recently suggested associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
9
2
Order By: Relevance
“…3,11 However, in our study we found the opposite. A possible explanation for this For personal use only.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…3,11 However, in our study we found the opposite. A possible explanation for this For personal use only.…”
Section: Discussioncontrasting
confidence: 82%
“…As patients are often admitted to hospital for a short time after VT and are closely monitored thereafter, it is possible that increased medicalization can explain the high number of arterial cardiovascular diagnoses made in the first year after VT onset. This, too, would explain the difference in our findings compared with those from the study by Van Schouwenburg et al, 11 as we only used hard endpoints.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, many of the risk factors for arterial thrombosis are also risk factors for VTE, and in addition VTEs have additional risk factors such as obesity and cancer 4 5. Indeed, VTE is a risk factor for subsequent arterial thrombosis 6. Some risk factors (such as orthopaedic surgery, certain types of valve disease and cardioversion for atrial fibrillation (AF)) are so strong, that anticoagulation is mandatory 7…”
Section: Introductionmentioning
confidence: 99%